2020
DOI: 10.1177/2056305119886025
|View full text |Cite
|
Sign up to set email alerts
|

Social Media and Teens: A Needs Assessment Exploring the Potential Role of Social Media in Promoting Health

Abstract: Aims: Social media use is widespread in teens. But, few studies have developed recommendations on how social media can be used to promote teen health. The Philadelphia Ujima™ Coalition funded by the Office on Women’s Health conducted a needs assessment to explore social media as a health communication tool. This study aimed to identify (1) social media utilization practices, (2) strategies to effectively engage teens on social media, and (3) recommendations for teen health promotion on social media. Methods: A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
58
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(76 citation statements)
references
References 45 publications
(48 reference statements)
2
58
2
Order By: Relevance
“…Vadel et al [ 65 ] suggested that for nonprofit organizations, implementing a social media strategy can help achieve health promotion goals. In connection with “designing effective communication message” and “meeting the needs of beneficiaries”, scholars concluded that social media holds promise as an effective health promotion mechanism; however, information must be reliable and composed of attractive messages customized to meet the needs of the target audience [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Vadel et al [ 65 ] suggested that for nonprofit organizations, implementing a social media strategy can help achieve health promotion goals. In connection with “designing effective communication message” and “meeting the needs of beneficiaries”, scholars concluded that social media holds promise as an effective health promotion mechanism; however, information must be reliable and composed of attractive messages customized to meet the needs of the target audience [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some technologies (e.g., online gaming) may be positively associated with aspects of development including for children from vulnerable populations by allowing for social interactions that would not otherwise occur (Adelantado‐Renau et al, 2019). Online technologies may also be designed to promote healthy behaviors (Plaisime et al, 2020). Sufficiently supporting children who are frequent users of online technologies to engage in beneficial developmental activities including regular physical activity and consistent sleep routines may lessen the aforementioned potential harms.…”
Section: Potential Harms and Benefits Of Frequent Electronic Device Umentioning
confidence: 99%
“…Word choice must be within the developmental and cognitive ability of the target demographic. Content must reflect the priorities of adolescents, show empathy for their concerns, and be engaging and entertaining [ 24 ].…”
Section: Exploring Cerc As Applied To Adolescentsmentioning
confidence: 99%